The Use of Metacognitive Strategies in EFL Reading Comprehension - Muhammad Nafi Annury (Universitas Muhammadiyah Semarang, 2018)
The following study aims to find out which is the highest use of metacognitive reading strategies among the academic learners majoring in EFL students, Faculty of Education and Teacher Training UIN Walisongo Semarang. There is only one class which administered to this study. It consists of forty three students; ten male students and there are thirty three female students actually. First of all metacognition discusses the process of an individual in planning and managing oneself in order to achieve his or her goal. In the other words, metacognitive strategies are steps that learners take for improving their language performances. Based on SORS (Survey of Reading Strategies) questionnaire, there are four categories being scored in the reading metacognitive strategies. They are global reading strategies, problem-solving strategies,, and support reading strategies. The result showed that academic learners mostly apply the problem-solving strategies, followed by global reading strategies, and support reading strategies.